2014
DOI: 10.1016/j.jval.2014.08.637
|View full text |Cite
|
Sign up to set email alerts
|

A Decision-Focused Mixed Treatment Comparison (MTC) of Alternative Dpp-4 Inhibitors (Dpp-4i's) Used in Combination With Metformin or a Sulfonylurea for the Treatment of Type 2 Diabetes Mellitus (T2DM)

Abstract: Objectives: Network meta-analyses (NMA) provide estimates of comparative efficacy for multiple treatments based on an analysis of connected networks of trial comparisons. A key concern is the comparability of treatment effect estimates from different trials. Where there is both indirect and direct evidence for one or more comparisons ('loops' in the network) it is possible to evaluate empirically the 'consistency' of the network. MethOds: A variety of methods have been proposed to examine inconsistency includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There are different approaches around the world that combines molecules in order to control the glucose blood level and also many studies that showed pros and cons in these associations. As searching in the literature, we found an impressive number of articles that aimed the efficacy and safety of new DPP-4 inhibitoralogliptin, compared to existing DPP-4 inhibitors sitagliptin, saxagliptin, linagliptin, vidagliptin, in combination with metformin or sulfonylurea [19].…”
Section: Introductionmentioning
confidence: 99%
“…There are different approaches around the world that combines molecules in order to control the glucose blood level and also many studies that showed pros and cons in these associations. As searching in the literature, we found an impressive number of articles that aimed the efficacy and safety of new DPP-4 inhibitoralogliptin, compared to existing DPP-4 inhibitors sitagliptin, saxagliptin, linagliptin, vidagliptin, in combination with metformin or sulfonylurea [19].…”
Section: Introductionmentioning
confidence: 99%